2014
DOI: 10.1155/2014/720715
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Binding Sites of miR-619-5p, miR-5095, miR-5096, and miR-5585-3p in the mRNAs of Human Genes

Abstract: The binding of 2,578 human miRNAs with the mRNAs of 12,175 human genes was studied. It was established that miR-619-5p, miR-5095, miR-5096, and miR-5585-3p bind with high affinity to the mRNAs of the 1215, 832, 725, and 655 genes, respectively. These unique miRNAs have binding sites in the coding sequences and untranslated regions of mRNAs. The mRNAs of many genes have multiple miR-619-5p, miR-5095, miR-5096, and miR-5585-3p binding sites. Groups of mRNAs in which the ordering of the miR-619-5p, miR-5095, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
2
20
0
2
Order By: Relevance
“…Understanding their individual and collective roles is important when studying the development of this neoplasia. miR-5095 had the highest number of binding sites distributed throughout the human genome (Table 3), which is in accordance with previously reported data [66][67][68] where approximately 900 binding sites were identified; they are probably related to the expression of many target mRNAs and biological processes. Based on its extensive genomic distribution and low specificity in CC, miR-5095 is a good candidate to be used as an indicator of genetic variability within the human population.…”
Section: Mirna Binding Sites Associated With Cervical Cancersupporting
confidence: 92%
“…Understanding their individual and collective roles is important when studying the development of this neoplasia. miR-5095 had the highest number of binding sites distributed throughout the human genome (Table 3), which is in accordance with previously reported data [66][67][68] where approximately 900 binding sites were identified; they are probably related to the expression of many target mRNAs and biological processes. Based on its extensive genomic distribution and low specificity in CC, miR-5095 is a good candidate to be used as an indicator of genetic variability within the human population.…”
Section: Mirna Binding Sites Associated With Cervical Cancersupporting
confidence: 92%
“…miR-619-5p is a miRNA that binds with high affinity to the mRNAs of 1,215 genes, and miR-619-5p has binding sites in the coding sequences and UTRs of mRNAs (19). Bioinformatics analysis indicated that miR-619-5p has several binding sites on the 3'-UTR of MALAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have described the altered expression of miRNAs in cancer tissues compared with normal tissues (17,18), suggesting that these miRNAs may potentially indicate novel clinical diagnostic and prognostic markers. miRNA-619-5p (miR-619-5p) is a miRNA that binds with high affinity to the messenger (m)RNA of 1,215 genes, and miR-619-5p has binding sites in the coding sequences and untranslated regions (UTRs) of mRNAs (19).…”
Section: Introductionmentioning
confidence: 99%
“…Ранее было показано, что сайты связывания miR-5096 локализуются на 832 таргетных матричных РНК [13]. Возможно, такое достаточно большое количество сайтов связывания говорит нам о функциональной роли miR-5096 в качестве координатора экспрессии больших генных ансамблей.…”
Section: Serpine1unclassified